Negotiating Curriculum Flexibility in Islamic Early Childhood Education: Merdeka Curriculum Enactment, Faith-Based Adaptation, and School Readiness - Irsyad, Mohammad; Ridho Riyadi; Rafa Zahra Syaikha; Aprilia Kartika Sari; Rofiqotul Aini; Mohammed Khalil, Abdelmajid Idris (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2026)
Curriculum flexibility is often presented as a route to more responsive early childhood education, yet less is known about how such flexibility is made workable in faith-based institutions where national reform, religious identity, local culture, and family expectations intersect. This study examines the enactment of the Merdeka Curriculum in a Raudhatul Athfal institution in Pekalongan, Indonesia, with attention to how teachers and school leaders negotiate project-based learning, differentiated instruction, Islamic educational values, children’s participation, and parental expectations of early academic readiness. Using an instrumental single-case study design, data were collected at RA Islamic Center Kedungwuni through four semi-structured interviews with the school principal and a Group B teacher, six non-participant classroom observations conducted from 1 to 14 April 2024, and document analysis. Fifteen Group B children provided contextual observational data, but they were not interviewed. The data were analyzed through open coding, axial coding, and iterative thematic development, with trustworthiness supported by triangulation, member checking, thick description, reflexive notes, and an audit trail. The findings show that curriculum enactment was shaped by four interrelated conditions: teachers’ uneven confidence in using digital learning platforms, a gap between P5 project practice and project-module documentation, the need for socio-emotional scaffolding in choice-based learning, and the negotiation of play-based literacy and numeracy with perceived parental expectations for visible school readiness. The study argues that curriculum reform in faith-based early childhood education depends on policy flexibility, institutional mentoring, practical documentation, emotionally responsive pedagogy, and sustained parent-school communication.